Public service og politisk balance: En typologi - David Nicolas Hopmann (Journalistica, 2009)
In an effort to understand and categorize media bias and balance in broadcasting journalism, this literature review proposes a new typology of different types of political balance in the broadcasting media: a typology that is not only based on an examination of media content, but also an examination of antecedents. That is, media output should be analyzed as a function of input processes. A new typology will be presented covering concepts such as media bias and media balance. Hereby, a framework for classifying media content is outlined helping us to compare cases across media outlets and countries. Throughout the article, four empirical examples will be discussed. Focus is on West European public service media outlets and their coverage of election campaigns.